A Diagnostic Odyssey: Coccydynia Misdiagnosis and Its Tolls on Chronic Pelvic Pain - Ali , Liaquat; Malik , Sara Haider; Ahmed , Khaleel; Nasir , Sana (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter provides a detailed account of diagnostic complexities faced with misdiagnosed coccydynia leading to chronic pelvic pain, with a specific objective to contribute to medical literature and emphasizing the importance of early diagnosis and early management to improve patient outcomes and quality of life. Coccydynia is a disabling condition characterized by pain in the coccyx region of the spine. Persistent discomfort in the perineal region, known as chronic pelvic pain, typically lasts longer than six months and can have either visceral or somatic origins. It doesn't react well to traditional painkillers. We report a case of a 42-year-old female suffering from severe chronic pelvic pain for the previous 15 years, for which she had been prescribed multiple analgesics including opiates and she underwent multiple surgeries without any relief. She was a misdiagnosed case of coccygeal fracture which caused chronic pelvic pain for the past 15 y, and when treated with ganglion impar neurolysis gave her complete pain relief. Coccyx is a delicate and mobile bone which is supported by the sacrococcygeal ligament and has more chances of sprain. Trauma to the coccyx due to body positioning while being seated can also cause chronic sprain over the coccyx. At her one-month follow-up, she had NRS 1/10 and was completely pain-free.When making a differential diagnosis for chronic pelvic discomfort, especially in females who are fertile, coccydynia needs to be taken into account.